2014
DOI: 10.20533/ijds.2040.2570.2014.0120
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and Data Protection in E-commerce in Developing Nations: Evaluation of Different Data Protection Approaches

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Privacy and data protection regulations, which vary from country to country, also play a key role. They can affect consumers' perceptions of security and decisions to use e-commerce platforms [64][65][66][67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Privacy and data protection regulations, which vary from country to country, also play a key role. They can affect consumers' perceptions of security and decisions to use e-commerce platforms [64][65][66][67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These programmes are, in most cases, not easy to find and with the low literacy levels in Nigeria, HUs may not have the skills and knowledge to find these programmes. If these programmes are found, they are, in most cases, not comprehensive enough, and do not include all relevant security issues [6], and furthermore, a security illiterate person will not know of the need to search for these awareness programmes online, particularly as personal information security may not be an overly important issue for Nigerians [22,23]. From the discussion above, it is concluded that an awareness programme should be able to perform the following functions:…”
Section: Figure 2 Compulsory Secured Access To the Web For Internet mentioning
confidence: 99%
“…In fact, numerous business organizations throughout the world have had data breaches that resulted in data loss or destruction, legal liability, a decline in customer trust, or monetary losses. [1,2] Defects in data security and privacy can have a lasting negative impact on an organization's finance, not to mention its reputation, credibility, and relationships with its customers. Organizations (especially public organizations) must make sure that all data are safeguarded from unauthorized users in order to ensure operational efficiency and consistently meet the demands of the teeming public.…”
Section: Introductionmentioning
confidence: 99%